Cerebral palsy: social class differences in prevalence in relation to birthweight and severity of disability. Issue 3 (September 1990) - Dowding, V M; Barry, C
Abstract : STUDY OBJECTIVE--The aim of the study was to examine the possible influence of social class on the prevalence of cerebral palsy. DESIGN--The study was a retrospective population based survey of all cases of cerebral palsy. SETTING--The study involved all cases of cerebral palsy born to residents in the Eastern Health Board area of the Republic of Ireland between 1976 and 1981 inclusive. PATIENTS--There were 289 cases of cerebral palsy during the study period. Thirty one were excluded because they were attributable to postneonatal brain damage, leaving 258 children for analysis. Cases with uncertain diagnosis were excluded. MAIN RESULTS--There was a clear social class gradient in the overall prevalence of cerebral palsy, also evident in the individual syndromes of hemiplegia and diplegia. No such gradient was detected in the other syndromes, either singly or in combination. Among cases of low birthweight (less than or equal to 2500 g), the prevalence was the same across the social class range after allowing for the increased low birthweight rate in the lower social class categories. Among normal birthweight cases there was a strong positive association with decreasing social class. Intrauterine growth retardation seemed to be a factor in cerebral palsy in all social class groups. Prevalence of cerebral palsy severe enough to prevent walking by the fourth birthday, but not of cases ambulant by this age, increased with socioeconomic disadvantage. CONCLUSIONS--The clear social class gradients in hemiplegia and diplegia suggest that environmental factors play an important role in the aetiology of these syndromes, but there was no evidence of a contribution from this type of factor in the remaining types of cerebral palsy.